In vitro and in vivo characterization of new swine-origin H1N1 influenza viruses - Itoh, Yasushi; Shinya, Kyoko; Kiso, Maki; Watanabe, Tokiko; Sakoda, Yoshihiro; Hatta, Masato; Muramoto, Yukiko; Tamura, Daisuke; Sakai-Tagawa, Yuko; Noda, Takeshi; Sakabe, Saori; Imai, Masaki; et al. (Nature (London), 2009)
Pandemic virus characterized Analysis of a series of clinical isolates of the swine-origin H1N1 influenza virus reveals that in mammalian models (mice, ferrets and macaques) the current pandemic virus is associated with more severe disease than a seasonal H1N1 strain. The viruses can also infect pigs but do not cause clinical signs. All antivirus drugs tested, including Tamiflu, were effective in cell culture against the new virus, lending support to the use of these compounds as a first line of defence against the pandemic. On 11 June 2009 the World Health Organization declared that the infections caused by a new strain of influenza A virus closely related to swine viruses had reached pandemic levels. Here, one of the first US isolates of the new swine-origin H1N1 influenza virus (S-OIV) is characterized, as well as several other S-OIV isolates, both in vitro and in vivo . Influenza A viruses cause recurrent outbreaks at local or global scale with potentially severe consequences for human health and the global economy. Recently, a new strain of influenza A virus was detected that causes disease in and transmits among humans, probably owing to little or no pre-existing immunity to the new strain. On 11 June 2009 the World Health Organization declared that the infections caused by the new strain had reached pandemic proportion. Characterized as an influenza A virus of the H1N1 subtype, the genomic segments of the new strain were most closely related to swine viruses 1 . Most human infections with swine-origin H1N1 influenza viruses (S-OIVs) seem to be mild; however, a substantial number of hospitalized individuals do not have underlying health issues, attesting to the pathogenic potential of S-OIVs. To achieve a better assessment of the risk posed by the new virus, we characterized one of the first US S-OIV isolates, A/California/04/09 (H1N1; hereafter referred to as CA04), as well as several other S-OIV isolates, in vitro and in vivo . In mice and ferrets, CA04 and other S-OIV isolates tested replicate more efficiently than a currently circulating human H1N1 virus. In addition, CA04 replicates efficiently in non-human primates, causes more severe pathological lesions in the lungs of infected mice, ferrets and non-human primates than a currently circulating human H1N1 virus, and transmits among ferrets. In specific-pathogen-free miniature pigs, CA04 replicates without clinical symptoms. The assessment of human sera from different age groups suggests that infection with human H1N1 viruses antigenically closely related to viruses circulating in 1918 confers neutralizing antibody activity to CA04. Finally, we show that CA04 is sensitive to approved and experimental antiviral drugs, suggesting that these compounds could function as a first line of defence against the recently declared S-OIV pandemic.